Crowdfunding Among Event Entrepreneurs: A Conceptual Paper - Hafizi Zamri, M; Mohamad Basir, F A; Anak Agam, D; Daim Darson, M (KnE Social Sciences, 2018)
This paper aims to uncover the benefits of crowdfunding among Event Entrepreneurs in Malaysia. The study reviews literature on the definition, discussion and its revolution related to capital -raising, networking, investment, and crowdfunding among Event Entrepreneurs. The method used for this paper is based on literature reviews from journal articles, conference proceedings, newspaper, books and internet search related to this research area. The conceptual framework is recommended in the end of the paper as it allows reader to understand how the benefits will affects towards crowdfunding among Event Entrepreneurs. Hence, it will provide more research interest in crowdfunding in the future. Keywords: crowdfunding, event, event crowdfunding